Current Status of Chimeric Antigen Receptor T-Cell Therapy in Multiple Myeloma. (May 2020) - Jindal, Vishal; Khoury, John; Gupta, Ruby; Jaiyesimi, Ishmael
Abstract : Multiple myeloma (MM) is an incurable malignancy of plasma cells. Recently multiple new therapeutic options have been introduced which was able to improve overall survival but ultimately patient become refractory specifically in patients with poor cytogenetics. Therefore, novel therapeutic options like immunotherapy are needed to improve outcomes. Chimeric antigen receptor (CAR) T-cell therapy is immunotherapy in which T cell are genetically engineered against a tumor-specific antigen and transfused back to the patient to mount major histocompatibility complex-independent cancer-specific immune response. The success of CAR T-cell therapy in lymphoid malignancies encouraged its development in MM. Most of the clinical studies target B-cell maturation antigen in relapsed refractory MM and relapse is the major issue. In this article, we will present the basics of CAR T-cell therapy, the most recent clinical and preclinical data, and we will discuss the future therapeutic realm of CAR T cells in MM.